Modern aspects of the development of East Kazakhstan agro-industrial complex - Denissova, О.K.; Madiyarova, E.S.; Sizov, M.V.; Stefaniski, Р.R. (BUKETOV BUSINESS REVIEW, 2018)
The article considers modern aspects of development process of agro-industrial complex, both in the Republic of Kazakhstan and East Kazakhstan region. The important role of agriculture in the economic and social sphere of any state is shown, which is one of the basic branches of the economy, the primary goal of which is the production of high quality food products that are competitive both on the domestic and foreign markets.The successful solution of this task depends on the creation of a stable base for the production of agricultural products, the availability of high-tech equipment, the creation of modern technological solutions for deep, non-waste processing of raw materials.The authors analyzed the current state of the agro-industrial sector of the country as a whole, and the region in particular, identified problems in the dynamics of its development.It is noted that the current level of agricultural development is characterized by developmental instability, low crop yields, low animal productivity, low inculcation of R & D, low degree of dissemination of modern agro-technical knowledge, concentration of agricultural production. In order to ensure the country's food security, it is necessary to switch to an innovative way of its development, in this connection, aspects of the competitiveness of the agro-industrial complex of Kazakhstan in the context of the globalization of the world economy.It was proposed to use also secondary raw materials of livestock for the formation of the potential of import substitution of the economy of the Republic of Kazakhstan.